Os sistemas completos de desigualdades propostos por Santaló - Santos, Bruno Mendonça Rey dos (Universidade Federal de São Carlos, 2007)
In 1961, Santaló[21] suggested that, considering the family of the convex bodies in R2, it was found a complete system of inequalities for each pair and each triple of the functions area, perimeter, diameter, inradius, circunradius and minimal width. In this work, we applied the technique developed by Blaschke[2] to solve all problems suggested by Santaló, those are solved until now.
Keywords: Geometria convexa; Conjuntos conexos; Desigualdades geométricas; Sistemas completos de desigualdades; CIENCIAS EXATAS E DA TERRA::MATEMATICA